Hubungan Antara Gaya Belajar, Kemandirian Belajar, Minat Belajar Terhadap Hasil Belajar Kelas VIII SMP Negeri Se-Kecamatan Labakkang - Ady, Achmar Chairil; Ismail, Ismail; Asham, Asham (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to analyze the relationship between learning styles, learning independence, and learning interest with the learning outcomes of class VIII students of junior high schools in Labakkang District. This study uses an ex post facto approach with a multiple correlational design. The population of the study was class VIII students of junior high schools in Labakkang District, totaling 653 students. The research sample was 101 students. Data were collected using questionnaires for learning styles, learning independence, and learning interest. Data analysis was carried out descriptively to categorize variables and inferentially to test the hypothesis. Prerequisite tests include data normality using the Kolmogorov-Smirnov test and linearity test. Hypothesis testing was carried out using simple regression analysis using Pearson Product Moment correlation and multiple linear regression analysis to see the simultaneous effect. The results of the study showed that (1) There is a significant relationship between learning styles, learning independence, and learning interest with student learning outcomes; (2) Found that students’ learning styles are dominated by visual and kinesthetic; (3) Independence and learning interest are in the medium category; (4) Learning outcomes in the high category.